If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 = 4y Reorder the terms: 4 + 4x = 4y Solving 4 + 4x = 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4x = -4 + 4y Combine like terms: 4 + -4 = 0 0 + 4x = -4 + 4y 4x = -4 + 4y Divide each side by '4'. x = -1 + y Simplifying x = -1 + y
| 12w^4+56w^3+32w^2=0 | | x^4=-25 | | 5x+13=42 | | 4y+10=46 | | 4u^3w^4+12u^9w^6x^9=0 | | 8.7+3.6-5.3= | | 12-10x=80-38x | | 3(4x+5)(3x-2)=0 | | 6(n+4)=8+7n | | 18d-4d-6d-8=2d | | -5m=4m+8 | | 7(m-3)=4(m+3) | | (2x-6)m=26 | | 4(z+2)-2z=10+3(z-3) | | 2(x+7)=40 | | -3.5(4a+1.9)a= | | -3.5(4a+1.9)= | | 4(x-8)=80 | | 8x^2+8x^6= | | (2x+3)(2-3x)-(2-3x)(4x+1)=0 | | y=3x+5y | | xy=3x+5y | | 32v^4-2u^4v^4=0 | | 3(w+3)=2w-2 | | y=10x^2+20x-1 | | 4x^2-25+6=0 | | 3x^2+16x=0 | | 3.7x=4.81 | | 14-(3m+6)=2+2m-19 | | -3.3y=6.6 | | 2=5x-3y | | -3.1y=21.7 |